THE EFFECT OF RETURN ON EQUITY (ROE), DIVIDEND PAYOUT RATIO (DPR), RISK BASED CAPITAL (RBC), AND DEBT EQUITY RATIO (DER) ON COMPANY VALUE IN INSURANCE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) PERIOD 2016-2020 - Yuliana, Visna; Fauzia, Rindiany; Nurmaulyna, Rizka; Khairunnisa, Sarah; Arialdi, Rapli; Widajatun, Vincentia Wahju (CENTRAL ASIA AND THE CAUCASUS, 2022)
Reason of this observe is to research the effect on firm price the usage of the ratio Price Book Value (PBV). The value of the enterprise in this situation the PBV ratio is one indication of a good organization if investors are willing to shop for stocks whose price is more steeply priced than the book value. The variables of this research are Return On Equity (ROE), Risk Based Capital (RBC), Dividend Payout Ratio (DPR), Debt to Equity Ratio (DER). Based totally on the purposive sampling approach, a sample of 6 companies was selected, with the criteria of insurance companies listed on the IDX in a row throughout the 2016-2020 period and insurance companies distributing dividends. In this study the data used is panel data. The source of this fact is acquired from the reputable website www.idx.co.id in the form of economic statements of coverage groups for 2016, 2017, 2018, 2019 and 2020 published on the Indonesia Stock change.Based at the consequence of the observe, Return On Equity (ROE) has a high quality and full size effect on firm value in insurance companies indexed on the IDX. Dividend payout ratio (DPR) has a negative and insignificant effect on firm value in insurance companies listed on the IDX. Risk Based Capital (RBC) has a positive and huge impact on firm value in insurance bussiness indexed on the IDX. Debt to Equity Ratio (DER) has a negative and insignificant impact on firm value in insurance groups listed on the IDX.